2023
DOI: 10.1109/jstqe.2022.3185169
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum generation in a varying dispersion waveguide for multi-species gas spectroscopy

Abstract: We report the experimental generation of a broadband and flat mid-infrared supercontinuum in a silicongermanium-on-silicon two-stage waveguide. Our particular design combines a short and narrow waveguide section for efficient supercontinuum generation, and an inverse tapered section that promotes the generation of two spectrally shifted dispersive waves along the propagation direction, leading to an overall broader and flatter supercontinuum. The experimentally generated supercontinuum extended from 2.4 to 5.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this work, we chose the Si 3 N 4 platform since it has shown a good compatibility for hybrid integration of 2D GO films. [52,56,68] Compared to silicon that has a relatively small bandgap of ≈1.1 eV, [69,70] Si 3 N 4 has a large bandgap of ≈5.0 eV [48,71] that yields low TPA in the near infrared region. We fabricated Si 3 N 4 waveguides in a process based on chemical-physical multistep annealing, encapsulation, and a tailored fluorocarbon dry etching, as reported previously.…”
Section: Device Design and Fabricationmentioning
confidence: 99%
“…In this work, we chose the Si 3 N 4 platform since it has shown a good compatibility for hybrid integration of 2D GO films. [52,56,68] Compared to silicon that has a relatively small bandgap of ≈1.1 eV, [69,70] Si 3 N 4 has a large bandgap of ≈5.0 eV [48,71] that yields low TPA in the near infrared region. We fabricated Si 3 N 4 waveguides in a process based on chemical-physical multistep annealing, encapsulation, and a tailored fluorocarbon dry etching, as reported previously.…”
Section: Device Design and Fabricationmentioning
confidence: 99%
“…We designed a multi stage waveguide (anomalous dispersion section followed by a varying width section resulting in a varying dispersion from anomalous to normal) to simultaneously increase the bandwidth of the generated SC and improve its spectral flatness. We exploited such SC for a proof-of-principle demonstration of multi-species gas (water vapour and carbon dioxide) spectroscopy in our laboratory environment [5]. We are currently exploring heterogeneous integration schemes with phase change material to dynamically control the waveguide dispersion state and therefore the supercontinuum spectral and temporal properties (Figure 3).…”
Section: Ge-based Light Sourcesmentioning
confidence: 99%
“…In both dispersion regimes, the spectral bandwidth saturated after a propagation distance of ∼20 mm, as a consequence of the waveguide dispersion, and of the linear and nonlinear losses. Recently, the same group proposed a two-stage design ( Figure 12(e) ), in order to combine the broad bandwidth provided by the anomalous dispersion with the flatter spectral shape typical of SCG in the ANDi regime [ 88 ]. The authors demonstrated a 40% increase in the SCG efficiency with such a dispersion-managed waveguide, and harnessed the improved spectral properties of the SC for the simultaneous detection of water vapor and CO 2 ( Figure 12(f) ).…”
Section: Supercontinuum Generation In Si-photonicsmentioning
confidence: 99%
“…By immersing the waveguide in chloroform solutions, the overtone absorption peak centered at 1695 nm was used to quantify the performance of the device, providing a proof-of-principle of such combined platform, albeit with limited performance at this point owing to the high loss of the waveguide and the weak evanescent field. The potential of MIR SCG in SiGe waveguides for direct absorption spectroscopy was also demonstrated with a proof-of-principle experiment [ 88 ]. Using 2.5–5 μm light directly emitted by SCG in dispersion engineered SiGe waveguides, the absorption fingerprint of both water and CO 2 could be detected and identified in parallel.…”
Section: Applications Of Chip-based Supercontinuummentioning
confidence: 99%